Analysis of Employee Performance in Improving Public Services at the Perbaungan District Office, Serdang Bedagai Regency - Lubis, Muhammad Ardiansyah; Lubis, Maksum Syahri; Batubara, Beby Masitho (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze employee performance in improving public services at the Sub-District Office of Perbaungan, Serdang Bedagai Regency. The research focuses on five employee performance indicators based on T.R. Mitchell’s theory, namely: quality of work, timeliness, initiative, capability, and communication. The method used is a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The research informants consist of the sub-district head, sub-district secretary, section heads, and members of the public as service recipients.The results of the study indicate that, in general, employee performance in delivering public services has shown significant improvement, particularly in the aspects of work quality and communication. However, challenges remain in the areas of timeliness and the use of technology in service delivery. Inhibiting factors to employee performance include limited human resources, lack of supporting facilities, and insufficient ongoing training and evaluation.